Flow Cytometric Analysis of Efflux by Dye Accumulation - Whittle, Emily E.; Legood, Simon W.; Alav, Ilyas; Dulyayangkul, Punyawee; Overton, Tim W.; Blair, Jessica M. A. (Frontiers in Microbiology, 2019)
Gram-negative infections are increasingly difficult to treat because of their impermeable outer membranes (OM) and efflux pumps which maintain a low intracellular accumulation of antibiotics within cells. Historically, measurement of accumulation of drugs or dyes within Gram-negative cells has concentrated on analyzing whole bacterial populations. Here, we have developed a method to measure the intracellular accumulation of ethidium bromide, a fluorescent DNA intercalating dye, in single cells using flow cytometry. Early exponentional bacterial cells were stained with SYTOTM 84 to easily separate cells from background cell debris. Ethidium bromide fluorescence was then measured within the SYTOTM 84 positive population to measure accumulation. In S. Typhimurium SL1344, ethidium bromide accumulation was low, however in a number of efflux mutants, accumulation of ethidium bromide increased more than 2-fold, comparable to previous whole population analysis of accumulation. We demonstrate simultaneous measurement of ethidium bromide accumulation and GFP allowing quantification of gene expression or other facets of phenotype in single cells. In addition, we show here that this assay can be adapted for use with efflux inhibitors, with both Gram-negative and Gram-positive bacteria, and with other fluorescent substrates with different fluorescence spectra.